Digital education and developing awareness of electronic risks from a social service perspective (Field study in the city of Baqubah) (Journal of the College of Education for Women, 2025)
The current research aims to identify what digital education is, and diagnose the challenges it faces in the process of developing awareness of electronic risks, as well as knowing digital ethics and its importance in building a healthy digital society, and employing the fields of the social work profession in raising levels of awareness of electronic risks among students. This research is one of Descriptive and analytical research that relies on the use of the social survey method using a purposive sample method that reached (200) respondents from male and female teachers working within the secondary staff in the General Directorate of Education of Diyala Governorate in the district of Baqubah and its environs. The researcher intended to build a scale (digital education and awareness of electronic risks), which It consists of (30) items distributed equally among three areas, after the form was subjected to the necessary statistical tests to verify its ability to measure what it was designed for. The research concluded that there are statistically significant differences between the areas of digital education and its role in developing awareness of electronic risks, The general trend of the respondents, each within their educational specialization, towards employing social service roles in developing awareness of electronic risks through interest in digital education was moderate.